Antioxidation enhancement and siliconization mitigation for SiC coated C/C composites via a nano-structural SiC porous layer. (January 2022) - Li, Tao; Zhang, Yulei; Fu, Yanqin; Sun, Jia
Abstract: A reactive nano-structural SiC porous layer on C/C surface was pre-prepared via a slurry-dipping and reaction-sintering method, using Si, C and Al2 O3 powders as raw materials. Pre-introduction of nano-structural SiC porous layer helped to form a dense sintered SiC coating by the pack cementation (PC), which provided excellent oxidation protection for C/C substrate under different conditions at 1773 K and mitigated the siliconization reaction of free silicon during the PC process. Results showed that the modified SiC coating had a mass loss of only ~0.03% after 50 thermal cycles between room temperature and 1773 K in air. And the mass loss reduced by ~4.31 and ~2.25 times after isothermal oxidation in dry air and wet oxygen atmosphere at 1773 K, respectively. Furthermore, because of the delaying effect of SiC porous layer on free silicon infiltrating into C/C substrate, the bending strength of modified SiC-coated C/C composites has increased by 93.0%. Highlights: A nano-structural SiC porous layer was fabricated via a facile route. Introducing nano-structural porous layer enhances the densification of SiC coating. The inhibiting effect of SiC layer on siliconization erosion improves the mechanical properties of coated samples.